1987
DOI: 10.1071/ea9870045
|View full text |Cite
|
Sign up to set email alerts
|

A rat bioassay for screening tropical legume forages and seeds for palatability and toxicity

Abstract: A rapid evaluation of palatability and apparent toxicity of forage legumes, using a rat bioassay and requiring only 400 g of dried forage or 100 g of seed, is described. Vegetative material is included as 20%, or seed as 5%, of a nutritionally complete, 12% protein (casein) diet for rats. Voluntary intake and weight gain of rats on test diets are compared with results from standard diets given ad libitum and at restricted rates. It proved possible to distinguish toxicity from simple unpalatability by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Sunn hemp seeds and pods may contain pyrrolizidine alkaloids (van Wyk & Verdoorn, 1990) which can negatively affect animal performance. Several studies have shown animal intake of this legume without adverse effects if consumed in the vegetative stages with no inflorescence (Burke, Mosjidis, Miller, & Casey, 2011;Purseglove, 1981;Strickland, Lambourne, & Ratcliff, 1987).…”
Section: Core Ideasmentioning
confidence: 99%
“…Sunn hemp seeds and pods may contain pyrrolizidine alkaloids (van Wyk & Verdoorn, 1990) which can negatively affect animal performance. Several studies have shown animal intake of this legume without adverse effects if consumed in the vegetative stages with no inflorescence (Burke, Mosjidis, Miller, & Casey, 2011;Purseglove, 1981;Strickland, Lambourne, & Ratcliff, 1987).…”
Section: Core Ideasmentioning
confidence: 99%
“…Many Crotalaria species have been found to be toxic to animals mainly because of high pyrrolizidine alkaloid content. Strickland et al (1987) established that about 50% of the Crotalaria species they tested had toxic plant tissue or seeds or both. For example, Ritchey et al (1941) determined that feeding C. spectabilis seed was toxic to cattle, chickens, and game birds, and C. retusa seeds were toxic to chickens.…”
Section: Seed Toxicitymentioning
confidence: 99%
“…In summary, there are two types of evidence indicating that C. juncea seeds do not cause acute toxicity as reported for other Crotalaria species, particularly some species introduced to the United States such as C. spectabilis and C. retusa (Ritchey et al, 1941; Hooper and Scanlan, 1977; Williams and Molyneux, 1987) (Table 1). The first set of evidence comes from the reports that found no or low pyrrolizidine alkaloids levels in seeds and other plant parts in a large number of populations developed in several countries (Adams and Gianturco, 1956; Pilbeam and Bell, 1979b; Strickland et al, 1987; Williams and Molyneux, 1987; Ji et al, 2005; Nurhayati and Ober, 2005). Second, toxicological studies conducted with animals, particularly chickens that are very susceptible to pyrrolizidine alkaloids, demonstrated lack of acute toxic effects (Williams and Molyneux, 1987; Hess and Mosjidis, 2008).…”
Section: Seed Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Strictland et al (1987) menyatakan bahwa sekitar 50% spesies Indigofera dilaporkan dapat menyebabkan keracunan dan penurunan palatabilitas pada hewan. Namun demikian, laporan penelitian Strictland et al (1987) tersebut menggunakan tikus sebagai hewan coba sehingga sulit untuk disimpulkan pada ternak ruminansia dan lebih tepat pada hewan monogastrik. Dengan demikian hasil penelitian yang saling bertentangan tersebut masih membutuhkan kajian kajian dan penelitian untuk membuktikan seberapa jumlah spesies Indigofera yang dapat menimbulkan keracunan pada ternak ruminansia.…”
Section: Dampak Indospicine Pada Ternakunclassified